Historical Culture, Structure of Narratives, and the Use of history on the Construction of Historical Consciousness: An Empirical Study in Indonesian Contexts - Nur Fatah Abidin (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2025)
This paper reports an empirical investigation of the epistemological aspect of historical consciousness, particularly on the relationship between three manifestations of historical consciousness namely narrative, the uses of history, and historical culture on the construction of historical consciousness. The main question addressed in this paper is about to what extent historical cultures, as the representation of cultural achievement, shape an individual's historical consciousness, which represents the anthropological universal aspect. This research departs from the theoretical debate on historical consciousness as an anthropological universal versus historical consciousness as a cultural achievement of Western civilization. Based on Jorn Rusen’s (2004) theoretical assumptions regarding the interrelation of historical narrative, the use of history, and historical culture, this study empirically demonstrates the connection between these three variables through comparisons and differences found in the research subjects. To answer this question, a qualitative research project based on a descriptive approach was used as a research method to observe students' narratives, uses of history, and historical culture in the History Study Program (HSP) and the History Education Study Program (HESP) at Sebelas Maret University in which those study programs have a different strand of the curriculum. The findings reveal differences in historical narratives and the use of history between students from the two study programs. This research shows the differences in narratives and uses of history between students from those two study programs. Students from the HSP tend to use critical standpoints to understand history. Meanwhile, students from the HESP, which stands on education and history, tend to understand history in a normative way. The differences prove that historical culture, which is represented by the Curriculum of the study programs, has constructed students' historical consciousness to be critical and normative. This also shows the encounter between cultural achievement and the anthropological aspect of humans in the construction of historical consciousness.